2007
DOI: 10.3892/ijo.30.4.873
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tumor oxygenation on hypoxia imaging in murine squamous cell carcinoma using [64Cu]Cu-ATSM or [18F]Fluoromisonidazole positron emission tomography

Abstract: [ 64 Cu]Cu(II)-ATSM (64 Cu-ATSM) and [18F]-Fluoromisonidazole (18 F-FMiso) tumor binding as assessed by positron emisson topography (PET) was used to determine the responsiveness of each probe to modulation in tumor oxygenation levels in the SCCVII tumor model. Animals bearing the SCCVII tumor were injected with 64 Cu-ATSM or 18 F-FMiso followed by dynamic small animal PET imaging. Animals were imaged with both agents using different inspired oxygen mixtures (air, 10% oxygen, carbogen) which modulated tumor hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 24 publications
2
44
0
Order By: Relevance
“…Our group has shown that the correlation of Cu-ATSM with hypoxia is tumor-dependent in rodent tumor models [17]. Similar findings were recently reported by Matsumoto et al [18], who found differences between the distribution of 64 Cu-ATSM and 18 F-fluoromisonidazole for measuring hypoxia in a murine squamous cell carcinoma model.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our group has shown that the correlation of Cu-ATSM with hypoxia is tumor-dependent in rodent tumor models [17]. Similar findings were recently reported by Matsumoto et al [18], who found differences between the distribution of 64 Cu-ATSM and 18 F-fluoromisonidazole for measuring hypoxia in a murine squamous cell carcinoma model.…”
Section: Discussionsupporting
confidence: 76%
“…O'Donoghue et al [19] compared early and late imaging of 64 Cu-ATSM with 18 Ffluoromisonidazole in rat tumor models. Although early imaging of 64 Cu-ATSM correlated with 18 F-fluoromisonidazole in the FaDu tumor model, 64 Cu-ATSM needed to be performed much later (16)(17)(18)(19)(20) hours) to achieve a distribution similar to 18 F-fluoromisonidazole in the R3327-AT tumor model. One hypothesis to explain these differences is that the distribution of Cu-ATSM may be limited in certain tumors by reduced delivery of the radiotracer because of poor perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-lived radionuclides can be used for sequential measurements, whereas radionuclides with longer half lives do Table 2 for full names. Lewis et al [133] , Yuan et al [134] , Kersemans et al [135] , Matsumoto et al [136] Ballegeer et al [137] , Bowen et al [138] , Lewis et al [133] , Myerson et al [139] , O'Donoghue et al [72] Ballegeer et al [137] , Hansen et al [140] , Matsumoto et al [136] , McCall et al [66] , O'Donoghue et al [72] , Oh et al [74] , Yuan et al [134] Grigsby et al [141] , Tateishi et al [142] , Valtorta et al [143] , Weeks et al [144] Dence et al [145] , Kersemans et al [135] , Lewis et al [146] , Matsumoto et al [136] , O'Donoghue et al [72] Dehdashti et al [86] , Lohith et al [67] , Wong et al [80] , Zhang et al [81] Chao et al [147] , Dehdashti et al [148] , Dehdashti et al [149] , Dietz et al [150] , Grassi et al [151] , Grigsby et al [141] , Kositwattanarerk et al [152] , Laforest et al [153] , Lewis et al [154] , Minagawa et al [155] , Nyflot et al [156] [ Mahy et al [158] , Mahy et al …”
Section: F]fetnim and [mentioning
confidence: 99%
“…64 Cu-ATSM has a high tumor-to-background ratio and has shown promising results in small clinical studies, in which the tumor-to-muscle ratio was able to predict treatment outcome (11)(12)(13). However, the robustness of 64 Cu-ATSM as a marker of hypoxia has been questioned, because preclinical studies have reported temporal changes in tumor uptake and cell-type-specific differences in hypoxia selectivity (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Table 1 provides an overview of major studies using 64 Cu-ATSM in small-animal tumor xenograft models.…”
mentioning
confidence: 99%